2011
DOI: 10.4161/sgtp.19257
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and stabilization of Rho small GTPase proteins for solution NMR studies

Abstract: Rho GTPases of the Ras superfamily have important roles in regulating the organization of the actin filament system, morphogenesis and migration of cells. Structural details for these proteins are still emerging, and information on their dynamics in solution is much needed to understand the mechanisms underlying their signaling functions. This report reviews conditions for solution NMR studies of Rho GTPases and describes our optimization and stabilization of Rnd1 for such experiments. Rnd1 belongs to the Rnd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Cdc42 (Feltham et al 1997;Oswald 2006, 2007;Buck et al 2004). Rac1 (Thapar et al 2003;Bouguet-Bonnet and Buck, 2006;Modha et al 2008;Lian et al 2000) and RhoA Mazhab-Jafari et al 2010;Cierpicki et al 2009) have been extensively studied by solution NMR, direct NMR studies of other Rnd1 have only been very recently reported (Cao and Buck 2012). Although optimization made the protein more suitable for solution NMR study, it appears the Rnd1 protein is still more unstable and more dynamic than other GTPases, allowing us to only obtain partial assignments.…”
Section: Biological Contextmentioning
confidence: 97%
“…Cdc42 (Feltham et al 1997;Oswald 2006, 2007;Buck et al 2004). Rac1 (Thapar et al 2003;Bouguet-Bonnet and Buck, 2006;Modha et al 2008;Lian et al 2000) and RhoA Mazhab-Jafari et al 2010;Cierpicki et al 2009) have been extensively studied by solution NMR, direct NMR studies of other Rnd1 have only been very recently reported (Cao and Buck 2012). Although optimization made the protein more suitable for solution NMR study, it appears the Rnd1 protein is still more unstable and more dynamic than other GTPases, allowing us to only obtain partial assignments.…”
Section: Biological Contextmentioning
confidence: 97%